2019
DOI: 10.1111/1756-185x.13776
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of direct cost of managing rheumatoid arthritis treatment to Pakistani patients using real‐world follow‐up data

Abstract: Objective This study aimed to estimate annual direct cost attributed to rheumatoid arthritis (RA) treatment from a patient's perspective using real‐world patient follow‐up data from hospitals’ electronic database. Methods A prospective 1‐year study was conducted in rheumatology clinics of tertiary care hospitals of Karachi, Pakistan. Cost‐of‐illness methodology was used and all patient data related to costs of rheumatologist visits, physical therapy sessions, medications, assistive devices and laboratory inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Finally, the direct costs of RA management were $ 235.1. The results showed that physiotherapy accounted for the highest percentage of costs, and drugs accounted for 7.1% of the costs, and this is inconsistent with the results of the present study [35]. Catay et al (2012) conducted a study on 165 patients in Argentina and found that the mean DMC and DNMC costs were $ 1,862 and $ 222, respectively.…”
Section: Discussioncontrasting
confidence: 95%
“…Finally, the direct costs of RA management were $ 235.1. The results showed that physiotherapy accounted for the highest percentage of costs, and drugs accounted for 7.1% of the costs, and this is inconsistent with the results of the present study [35]. Catay et al (2012) conducted a study on 165 patients in Argentina and found that the mean DMC and DNMC costs were $ 1,862 and $ 222, respectively.…”
Section: Discussioncontrasting
confidence: 95%
“…It progressively deteriorates the joints and causes joint deformity that reduces mobility. The disease is ranked as one of the leading causes of disability and is linked to productivity losses and economic burden (Guo et al, 2018;Naqvi et al, 2020). Globally, the disease prevalence ranges from 0.5 to 1% with slight variation region-wise.…”
Section: Introductionmentioning
confidence: 99%
“…In worst case, it may contribute to productivity loss, early retirement, economic burden, etc. (Naqvi et al, 2017;Naqvi et al, 2020). Hence, monitoring of patients' adherence is important to select appropriate clinical course and ensure positive treatment outcomes, i.e., lower disease activity and higher HRQoL (Salt et al, 2012;Naqvi et al, 2019d).…”
Section: Introductionmentioning
confidence: 99%